2011
DOI: 10.5114/aoms.2011.23417
|View full text |Cite
|
Sign up to set email alerts
|

A long-term study of bone mineral density in patients with phenylketonuria under diet therapy

Abstract: IntroductionDietary control of classic phenylketonuria (PKU) needs restriction of natural proteins; adequate protein intake is achieved by adding low phenylalanine (phe) formulae. The adequacy of this diet for normal bone mineralization had not been sufficiently evaluated. Our aim was to evaluate and follow up bone mineral density (BMD) in children and adolescents with PKU within a 2-year time interval to assess the adequacy of a phenylalanine restricted diet for bone mineralization and to search for a possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
(42 reference statements)
2
28
1
Order By: Relevance
“…We found no difference in BMD Z-score by PAH deficiency severity, similar to what has been reported in two recent studies (de Groot et al 2012; Miras et al 2013), and in contrast to the previously held belief that more severe patients will have lower BMD (Zeman et al 1999;Koura et al 2011). In addition, there was no difference in BMD Z-score by age category, as reported by other studies in the literature (Zeman et al 1999;de Groot et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…We found no difference in BMD Z-score by PAH deficiency severity, similar to what has been reported in two recent studies (de Groot et al 2012; Miras et al 2013), and in contrast to the previously held belief that more severe patients will have lower BMD (Zeman et al 1999;Koura et al 2011). In addition, there was no difference in BMD Z-score by age category, as reported by other studies in the literature (Zeman et al 1999;de Groot et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Higher intake of food phenylalanine correlated to a BTM ratio favoring resorption (p-value ¼ 0.017) while better compliance with medical food correlated to a BTM ratio favoring formation (p-value ¼ 0.056) suggesting following diet is critical. DXA showed normal BMD for age in all subjects and a mean total BMD Z-score of 0.045 (range À1.9-2.3) contradicting low BMD found in previous studies (Carson et al 1990;Zeman et al 1999;Perez-Duenas et al 2002;Koura et al 2011) but in line with more recent reports (Demirdas et al 2015;Geiger et al 2016). We defined low BMD by ISCD criteria (Z-score <À2) instead of alternative definitions used in previous studies (Demirdas et al 2015).…”
Section: Discussioncontrasting
confidence: 37%
“…Three studies (Allen et al 1994; Hillman et al 1996; Koura et al 2011) reported spine BMD in 67 individuals with PKU and 161 healthy age and gender matched controls (Table 1). A Forest plot of these three studies (Figure 2) demonstrated that spine BMD was 0.100 g/cm 2 lower (95% CI, −0.110, −0.090 g/cm 2 ) in subjects with PKU, compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (McMurry et al 1992; Allen et al 1994; Hillman et al 1996; Al-Qadreh et al 1998; Barat et al 2002; Perez-Duenas et al 2002; Millet et al 2005; Modan-Moses et al 2007; Adamczyk et al 2010; Lage et al 2010; Koura et al 2011; de Groot et al 2012) in 412 PKU patients evaluated correlations between BMD and phenylalanine levels (Table 3). Three of 12 studies (McMurry et al 1992; Al-Qadreh et al 1998; Adamczyk et al 2010) in 119 of 412 (29%) PKU patients reported an inverse association between phenylalanine and BMD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation